United registration database in virtual cloud of information system of education establishment - Толстых, В. К.; Кожемякин, А. Ю. (Problems of Informatization and Control, 2012)
The problem of data collection and support for up to date registration data of participants in the educational process. Is proposed developing of information systems in education to organize access to registration data in the form of contingent virtual cloud, using a single registration database.